PRIORITY SCOPE ANALYSIS FOR EFFECTIVE AND EFFICIENT FINANCING MANAGEMENT AS A STRATEGY FOR DEVELOPING ISLAMIC EDUCATIONAL INSTITUTIONS - Rifa'i, Moh (IZZI: Jurnal Ekonomi Islam, 2024)
It is important to analyze and determine the scope of program financing management priorities so that it can have implications for improving the development of educational institutions gradually and targeted. Program financing on a priority scale is the main step that must be decided. The research uses a qualitative approach with case studies. The researcher describes and analyzes the analysis process and what are the priority scopes in effective and efficient financing management. Direct participation with leaders and finance staff. The data collection technique is through interviews and observations while the analysis is carried out through data reduction, data presentation, conclusion drawn, and verification. The results of this study explain that the process of analyzing the scope of financing management priorities is carried out by determining the objectives of analysis, data reduction through the identification of priority programs, data collection, data presentation, conclusion making and verification. The priority scope of financing management consists of priority scale program financing planning including needs analysis, and budgeting, and priority scale program cost planning, financing organization consists of organizing programs and estimating their costs, direction with the implementation of variance analysis, the use of information technology, cooperation and networking, identification of problems and opportunities, as well as the implementation of the scope of priorities consisting of budget preparation, bookkeeping, auditing, and accountability, and supervision consisting of budget control, supervision through bookkeeping and reporting, cash management, and stakeholder feedback.